Big data on campus : data analytics and decision making in higher education - Zheng, Henry Y.; Webber, Karen L. (Johns Hopkins University Press, 2020)
"This edited collection by leading data scientists and higher ed leaders explains what data analytics can contribute to improving the administration of colleges and universities. The book includes several case studies of effective data analytics as applied to the areas of admissions, enrollment and retention, student life and engagement, academic advising, and learning assessment"--